2019
DOI: 10.1177/0969733019851546
|View full text |Cite
|
Sign up to set email alerts
|

Defining compassionate nursing care

Abstract: Background: Compassion has long been advocated as a fundamental element in nursing practice and education. However, defining and translating compassion into caring practice by nursing students who are new to the clinical practice environment as part of their educational journey remain unclear. Objectives: The aim of this study was to explore how Chinese baccalaureate nursing students define and characterize compassionate care as they participate in their clinical practice. Methods: A descriptive qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…Further, a mathematical model is proposed to distribute the workload between the personnel. The aim is to guarantee more contact between nursing professionals and patients, and, ultimately, compassionate, committed care with a humane tone focused on particular needs (Su et al, 2020). In this research, we corroborate that the workload of nursing depends on the combination of the individual health condition of patients, particularly when it comes to a functional state, individual needs of nursing care, and the gravity of the symptoms (Morris et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…Further, a mathematical model is proposed to distribute the workload between the personnel. The aim is to guarantee more contact between nursing professionals and patients, and, ultimately, compassionate, committed care with a humane tone focused on particular needs (Su et al, 2020). In this research, we corroborate that the workload of nursing depends on the combination of the individual health condition of patients, particularly when it comes to a functional state, individual needs of nursing care, and the gravity of the symptoms (Morris et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…Compassionate care entails that nurses enter into the patients’ experience and ensure that patients maintain their independence and dignity (Lee & Seomun, 2016a ). For nursing students, a compassionate care involves empathy, alleviation of the suffering of the patients, attending to individualized nursing needs, utilizing therapeutic communication and stimulating benefits of the patient and the nurse (Su et al., 2020 ). Previous research reported that being compassionate enhances patient quality care and the nurse's well‐being (Pattison & Samuriwo, 2016 ).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Compassion is a virtue and a critical component of nursing care because it serves as the human and moral aspect of care (Su et al., 2020 ). Compassionate care is the “union of empathy related to and interacting with a nurse's desire to alleviate patients’ suffering, addressing individualized care needs, using therapeutic communication and promoting mutual benefits with their patients” (Su et al., 2020 , p. 491). Hence, future nurses should develop a caring behaviour and compassion in dealing with patients.…”
Section: Introductionmentioning
confidence: 99%
“…17 In spite of what has been described so far, in the literature, sometimes, compassion appears as a quality close to empathy, although they are not actually equivalent. 18 Empathy may be defined as the ability to understand and participate in someone else's emotional reality and feelings. 19 However, empathy is the indirect experience of someone else's emotions, but it does not necessarily entail a response to their suffering, and it does not involve the will to act.…”
Section: Introductionmentioning
confidence: 99%
“…23 This whole philosophical and religious journey of the concept of compassion is what leads us to the currently accepted definition of compassion in the field of health sciences. 7,10,18 Compassion is understood as openness and sensitivity to suffering, along with the desire and motivation to relieve it. 13,24 Currently, certain sciences such as bioethics, nursing, medical research, neuroscience, social psychology, contemplative sciences, and medical anthropology, among others, have taken an interest in this concept.…”
Section: Introductionmentioning
confidence: 99%